GREEN INFRASTRUKTUR IN THE GLOBAL ERA - Adelia Nur Safitri; Conny Damayanty; Andri Indrawan (International Journal of Business, Law and Political Science, 2024)
This research aims to determine the development and implementation of green infrastructure, regulations and policies on green infrastructure as well as challenges, obstacles and solutions to green infrastructure in Indonesia. Sustainable development that pays attention to the environment in the era of globalization is very important to be implemented, this is in line with the Sustainable Development Goals (SDGs) which are a global reference to achieve a better and sustainable life. One of the SDGs targets is goal number 9 regarding "Industry, Innovation, and Infrastructure". Qualitative research methods with literature study techniques are the methods used in research. This study reviews the development and implementation of green infrastructure, regulations and policies on green infrastructure as well as challenges, obstacles and solutions to green infrastructure in Indonesia. The results of the study reveal that green infrastructure has an important role in realizing the Sustainable Development Goals (SDGs) where with technology there is great potential in supporting the development of green infrastructure to be more effective, efficient and sustainable. The implementation of green infrastructure in Indonesia has begun to be carried out, but there are still various negative impacts caused by challenges and obstacles such as limited human resources who do not understand the green infrastructure and economic system, so based on previous research there is a solution to mitigate these negative impacts, namely by implementing the green infrastructure framework.